Stress and Depression in Ohio Social Workers during the COVID-19 Pandemic: The Buffering Role of Social Connectedness. Issue 1 (19th December 2022) - Park, Daejun; Lee, Mingun; Osborne, Kara; Minnick, Dane
Abstract: Although social workers have an elevated risk of infection with COVID-19, no previous studies have investigated the virus's impact on practitioners. Using survey data ( N = 441), this study identified associations between stress, depression, and COVID-related factors and explored the role of social connectedness as a moderator for mental health among Ohio social workers. The results of the study showed that among social workers with a positive COVID-19 diagnosis, 70 percent experienced moderate/high levels of stress, and 37 percent met the criteria for clinical depressive symptoms. Results from the multiple regression analyses showed that perceived stress was positively associated with a positive COVID-19 diagnosis for social workers, and depression was positively associated with working with a client with a positive COVID-19 diagnosis. An interaction effect was also identified between social connectedness and social workers' mental health. These findings suggest that the provision of individual or organizational interventions that emphasize social connectedness can help to protect social workers' mental health.